2014
DOI: 10.1111/fog.12082
|View full text |Cite
|
Sign up to set email alerts
|

Amazon River water in the northeastern Caribbean Sea and its effect on larval reef fish assemblages during April 2009

Abstract: During April to June 2009, a large bolus of Amazon River water impacted the northeastern Caribbean Sea. Shipboard observations collected near Saba Bank, the U.S. and British Virgin Islands, and the Anegada Passage showed low surface salinity (35.76 ± 0.05 Practical Salinity Unit (PSU)), elevated surface temperature (26.77 ± 0.14°C), high chlorophyll‐a (1.26 ± 0.21 mg m−3) and high dissolved oxygen (4.90 ± 0.06 mL L−1) in a 20‐ to 30‐m thick surface layer in the riverine plume. The water was ~1°C warmer, 1 PSU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 62 publications
(93 reference statements)
6
27
0
Order By: Relevance
“…Salinity is, in general, an ocean parameter less accurately reproduced by the model used here, which is partially due to the scarcity of salinity observations assimilated into the model. This is an important issue, given that regions off Puerto Rico are sensitive to different freshwater sources, such as the Amazon and Orinoco rivers [Kelly et al, 2000;Corredor et al, 2003;Balaguru et al, 2012a;Johns et al, 2014]. The assimilation of precipitation and fresh water sources in the model as well as the improvement in vertical discretization may enable a better representation of salinity features, such as the shallow low-salinity layer observed above 20 m.…”
Section: Modeling Resultsmentioning
confidence: 99%
“…Salinity is, in general, an ocean parameter less accurately reproduced by the model used here, which is partially due to the scarcity of salinity observations assimilated into the model. This is an important issue, given that regions off Puerto Rico are sensitive to different freshwater sources, such as the Amazon and Orinoco rivers [Kelly et al, 2000;Corredor et al, 2003;Balaguru et al, 2012a;Johns et al, 2014]. The assimilation of precipitation and fresh water sources in the model as well as the improvement in vertical discretization may enable a better representation of salinity features, such as the shallow low-salinity layer observed above 20 m.…”
Section: Modeling Resultsmentioning
confidence: 99%
“…Furthermore, the NBCR forms at about the same time which shunts drifters into the NECC. Drifters can reach the Lesser Antilles in summer either through a narrow coastal current (Guiana Current) or via rings which break off from the NBCR and drift northwestward to the Caribbean (Johns et al 2014). A ring break-off occurred in the first pelagic Sargassum incursion events of the Lesser Antilles in 2011 (Franks et al 2011), creating uncertainty in direction of incursion until model backtracking revealed its path.…”
Section: Figure 2 (A) Experiments Using Satellite Tracked Mixed-layermentioning
confidence: 99%
“…Most of the carangid species examined here spawn in neritic coastal waters, where most previous surveys have focused sampling effort in shallow water <100 m deep (Espinosa‐Fuentes & Flores‐Coto, ; Katsuragawa & Ekau, ; Leak, ; Shaw & Drullinger, ). In contrast, samples in this study were collected far offshore in depths ranging from 500 to 3,000 m. Thus, the gear types used here and areas sampled most likely captured late stage larvae to early/late juveniles that were either passively entrained in circulation patterns of the expansive river plume (Grimes & Finucane, ; Johns et al., ) or actively engaging in ontogenetic migrations from nearshore to offshore habitats (da Costa, Albieri, & Araújo, ) or aggregating in the hydrodynamic nutrient rich and productive frontal regions (Ditty et al., ; Raya & Sabates, ).…”
Section: Discussionmentioning
confidence: 92%
“…The commonalities and differences in species‐environment relationships were also exhibited in the RDA ordination plots, where S. setapinnis, C. crysos , and C. chrysurus were correlated positively with SST and SSHA, and negatively correlated with salinity whereas C. hippos was opposite of those three species. Other studies have demonstrated that river plume features can be characterized by low salinity and increased temperature (Johns et al., ). The higher abundance of S. setapinnis, C. crysos , and C. chrysurus post larvae at lower salinities and warmer SST suggests association with the river plume that could either result from passive entrainment of small buoyant larvae due to hydrodynamic convergence zones (Bakun, ; Govoni, Hoss, & Colby, ) or active seeking out of plume waters for feeding (Govoni & Chester, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation